Incorporating Sundanese Ethics into Political Leadership: An Analysis of Dedi Mulyadi's Leadership Style in West Java, Indonesia - Mahatva Yoga Adi Pradana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
This research aims to explain how the adoption of Sundanese ethical values is reflected in Dedi Mulyadi's leadership practices, from serving as the Regent of Karawang to carrying out his role as the Governor of West Java. The focus of the research is not only on the idea of ethics as a normative concept, but also on its application in politics, leadership legitimacy building, and culturally grounded power exercises. The research uses a qualitative case study approach with data collection through interviews, field observations, document review, and public response tracking in digital media, which is analysed with the help of Python and NVivo tools. The results of the study show that values such as silih asih, silih asah, and silih asuh (compassionate leadership, deliberative democracy, and social welfare) are seen in various policies, participatory programs, and communication patterns. These findings show that Sundanese ethics do not stop at the symbolic level, but they become a practical foundation in building leadership that is rooted in local culture and responsive to public needs. On the other hand, this study also shows that the integration of local values in political leadership can strengthen public trust, even when faced with modern political dynamics and demands.